The Effectiveness of Using Cort Program in Teaching Thinking in Solving Problems and Achievement of 8th Grade Students in Science Curriculum - AlRashdan, Oklah Mahmoud Ahmad; Baara, Hussein AbdelLatif (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed to investigate the effect of using the Cort program to teach thinking in science teaching on problem solving and achievement among eighth-grade students in the Central Badia Directorate. Central Badia Directorate. The study used two tools, one of them, a multiple-type test, and a sale; An example of a multiplication tool, which was applied to a sample of (60) students, The results of the study showed that there were statistically significant differences at the level of (α ≤ 0.05) in the achievement of eighth grade students attributed to the teaching method in favor of the CoRT program compared to the regular method, and in solving problems among eighth grade students attributed to the teaching method in favor of the CoRT program compared to the usual method. Based on the results, the researchers recommended using the remaining five parts of the program to study the effectiveness of the CoRT program in developing students' thinking in science.
Keywords: Cort program; achievement; problem solving